Vitamin D Status and Physical Functioning in Nursing Home Residents after Improved Adherence to the Vitamin D and Calcium Recommendation—A Quasiexperimental Study - Charlotte Mortensen; Anne Marie Beck; Inge Tetens; Charlotte Jeppesen; Søren Frank Jørgensen; Leif Kofoed Nielsen; Michael Kristensen (Journal of Nutrition and Metabolism)
Introduction. Dietary supplements with vitamin and calcium are recommended to nursing home residents in Denmark, but adherence to the recommendation is low. In a previous part of this study, we reported improved adherence by means of The Model for Improvement leading to increased awareness and change of workflows at two nursing homes. However, potential effects of this improved adherence are unknown. Objective. The objective of this substudy was to investigate if the improved adherence to the recommendation affected vitamin D status, muscle strength, and physical functioning of the residents. Methods. This was a 20-week quasiexperimental study involving 40 residents from two Danish nursing homes. Baseline and endpoint measurements took place in October 2021 and March 2022, respectively. Outcomes were number of residents taking vitamin D and calcium supplements; vitamin D status; handgrip strength; and physical functioning with timed-up-and-go test and 30-second chair stand test. Results. Prevalence of vitamin D supplement users increased from 45 to 78% (mean dose 41 μg) and of calcium supplement users from 40 to 72% (mean dose 769 mg) (both P=0.002). Among those having blood sampled at both baseline and endpoint (n = 30), mean vitamin D status increased from 66.6 ± 31.7 nmol/L to 82.8 ± 26.3 nmol/L (P<0.001), and more residents were vitamin D sufficient at endpoint (90 vs. 63%, P=0.021). Endpoint vitamin D status among supplement users was 88.2 ± 22.2 nmol/L, which was higher compared to nonsupplement users (55.3 ± 30.4 nmol/L, P<0.01). No effects were seen on muscle strength or physical functioning. Conclusions. Increased supplementation with vitamin D using The Model for Improvement positively affected vitamin D status and prevalence of vitamin D sufficiency but did not affect muscle strength or physical functioning. Longer-term studies involving more residents are needed to investigate effects of improved adherence on these outcomes. This trial is registered with NCT04956705.